1973
DOI: 10.1111/j.1471-4159.1973.tb12126.x
|View full text |Cite
|
Sign up to set email alerts
|

The Activities of Butyrylcholinesterase and Carbonic Anhydrase, the Rate of Anaerobic Glycolysts, and the Question of a Constant Density of Glial Cells in Cerebral Cortices of Various Mammalian Species From Mouse to Whale

Abstract: Abstract— The question of a constant density of glial cells in mammalian cerebral cortex regardless of species was examined by surveying the cortical activities of two enzymes primarily localized to dial cells. The cortical activity of butyrylcholinesterase (EC 3.1.1.8) was essentially constant at a rate of approx. 0.1 μmol of butyrylthiocholine hydrolysed min‐1 g‐1 over the range of species from rat (brain wt., 1.6 g) to fin whale and sperm whale (brain wt., 6800 and 7800 g, respectively). Over the same range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
76
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(87 citation statements)
references
References 50 publications
11
76
0
Order By: Relevance
“…The slope of the regression line (Fig. 3) corresponds to what was found by Tower and Young (1973) when comparing brain weight with glial cell/neuron ratio between different mammals. The average glial cell/neuron ratio for the harbor porpoise and for the harp seal was 2.3/1 and 2.8/ 1, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…The slope of the regression line (Fig. 3) corresponds to what was found by Tower and Young (1973) when comparing brain weight with glial cell/neuron ratio between different mammals. The average glial cell/neuron ratio for the harbor porpoise and for the harp seal was 2.3/1 and 2.8/ 1, respectively.…”
Section: Discussionsupporting
confidence: 71%
“…If power given to repair per nucleotide or per codon is constant because of the limited spatial access to these domains, then it follows that power given to repair per DNA content is constant. For mammals, DNA content and glial cell size are roughly invariant, but brain neuronal cell size appears to vary as M b 1/4 (43)(44)(45)(46)(47). Consequently, within this scenario, power given to repair per unit volume, P R , would still be a constant for glial cells but would decrease as M b Ϫ1/4 for neuronal cells.…”
Section: Methodsmentioning
confidence: 99%
“…Tamura and his colleagues suggested that neuronal packing density may be one factor causing species variations in flow threshold for the occur rence of brain damage. It is of interest, but may be coincidental, that the species ranking for flow threshold which now emerges (baboon-cat-rat) is similar to that for glial/neuronal ratio (Tower and Young, 1973). Further caution in the pursuit of this line of argument is necessary since the flow data on which the comparison is based were obtained by different methods (hydrogen clearance and au toradiography).…”
Section: Effects Of Occlusion On Kp and Relationships With Blood Flowmentioning
confidence: 99%